Wprowadzenie do post-koiné: nieantropocentryczne języki poezji - Jarzyna, Anita (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article is a cross-sectional study that analyses contemporary Polish poets’ metapoetic reflections on anthroponormative language and their ways of elaborating alternative ways of representing animals. They often unveil oppressive animalistic metaphors, i.a. writting as hunting, and create less obvious ones, for example the poem as an animal. This kind of image commits both the author and the reader of the poem to care – they are both somehow obligated not to objectify animals in their interpretations. By referring to poems (written by Magdalena Bielska, Stanisław Grochowiak, Ryszard Krynicki, Piotr Matywiecki, Krystyna Miłobędzka, Jacek Podsiadło, Wisława Szymborska, Eugeniusz Tkaczyszyn-Dycki) and inspiring essays by Tadeusz Sławek, the author of this article formulates and leads out a concept of post-koine, which is a language critical towards any too narrow idea of the community (koine), the language of a new interspecies community, an inclusive language devoid of violence against animals.